Molecular identification of Lodoicea maldivica (coco de mer) seeds - Mok Chuen-shing; Mak Chun-yin (BMC, 2011)
Abstract Background The edible endosperm of Lodoicea maldivica with the common name of coco de mer is used in Chinese medicine for treating cough. Native to Seychelles, Lodoicea maldivica seeds have commanded high prices for centuries due to its scarcity. This study aims to develop a molecular identification method for the authentication of Lodoicea maldivica seeds. Methods DNA was extracted from the sample. Two polymerase chain reaction (PCR) systems were developed to amplify a region of the chloroplast DNA and the nuclear phosphoribulokinase (PRK) region specific to Lodoicea maldivica respectively. DNA sequence of a sample was determined and compared with that of the Lodoicea maldivica reference material. Results The PRK gene of Lodoicea maldivica was successfully amplified and sequenced for identification. Conclusion A new molecular method for the identification of Lodoicea maldivica seeds in fresh, frozen or dried forms was developed.